THE GENDER ASPECT OF ASSURANCE OF DEMOCRATIC CIVIL CONTROL IN THE SECTOR OF SECURITY AND DEFENSE OF THE STATE - Bobrova, J.; Bobrov, J. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The effective command and control of the Armed Forces of Ukraine and other elements of the defense forces with the aim to achieve the high-level of defense capability of the state which are inextricably related with the appropriate normalization and exercising the practical events of democratic civil control of the military organization of the state.The process of reforming the defense sector is aimed at transforming the system of unified command and control and military command of the Armed Forces of Ukraine. The establishment of a new system of command and control provides for a clear delimitation of authority between the Ministry of Defense and the Armed Forces of Ukraine, the functioning of new types and branches of troops (forces). Additionally, it is provided for the separation of the functions of planning, generation and implementation of means and forces within the Armed Forces, and the Ministry of defense has transformed from the body of military command to the central body of executive authority, responsible for the reform and implementation of the state policy in the military sphere and the sphere of defense, the military policy in terms of staff, the technical policy and the policy in terms of defense purchases etc. One of the major tasks of the Ministry of Defense is the exercise within the framework of authority of democratic civil control of the activity of the Armed Forces of Ukraine, the military-political and administrative command and control of the military organization.The gender equality requires the establishment of equal rights and opportunities for men and women in the matters of military service, participation in the protection of the state – not only on a legislative but also on a practical level. For a long period of time the military profession was solely masculine. It has been related with the significant physical, moral-psychological pressure on a human being, the necessity to be firm in overcoming the hard and difficult daily military routine. Currently, the role of the woman in a society has undergone significant changes. The latter have also touched the military sphere. It is therefore the issue of democratic civil control of the military organization of the state is to be considered through the prism of its gender aspect. For the sole, gender element of this control is the finest measure of its effectiveness, the indicator of absolute control of civic society in the military sphere, which assures the accountability of military to civil personnel and totally includes the possibility of a military coup d’état in a state.
Keywords: democratic civil control, gender, sector of security and defense, Armed Forces of Ukraine, men, women